Produção de hidrogênio a partir da reforma a vapor do gás liquefeito de petróleo utilizando catalisadores suportados em céria-sílica - Moura, Lucas Gomes (2018)
Hydrogen production from the vapor reforming reaction of liquefied petroleum gas (LPG) was studied over nickel, platinum, rhodium and ruthenium-based catalysts supported on CeSiO2. CeSiO2 support was prepared by the co-precipitation method in order to obtain 75wt.% CeO2 and 25wt.% SiO2. The catalysts were prepared by wet impregnation technique of the support with precursors of nickel, platinum, rhodium and ruthenium metals as a result in catalysts with metal contents of 10, 1, 1 and 5wt.%, respectively. The samples were characterized by BET surface techniques, X-ray diffraction (XRD), temperature-programmed reduction (TPR) and X-ray absorption near edge structure spectroscopy at the L3 edge of Ce. LPG was represented as an equimolar mixture of propane and butane. The catalysts were tested for activity and catalytic stability and selectivity for products in the LPG reforming at 600 °C. The results of TPR and XANES on the Ce L3-edge showed that the addition of the metal in the support decreased CeO2 reduction temperature. Rh catalyst showed the lowest CeO2 reduction temperature, while Pt catalyst presented the highest reduction degree of CeO2, reaching a reduction of 55% at the end of the reduction at 500 °C. Ex situ XRD analysis was performed for the calcined samples and in situ XRD measurements were carried out during the process of reduction at 500 °C and steam reforming of propane at 600 °C. The diffractograms of all calcined samples exhibited peaks typical of CeO2 cubic phase. For Pt and Rh containing samples, no diffraction peaks related to the metals were identified which indicate high dispersion. However, Ni and Ru peaks were identified in the samples. The in situ XRD data indicated a small increase in the mean particle size of Ni0 and Ru0 after being subjected to reaction conditions. The activity tests performed for steam reforming of LPG at 400 °C show that the order of catalyst activity was Rh/CeSiO2> Ru/CeSiO2 ≈ Pt/CeSiO2> Ni/CeSiO2. The stability tests were performed for steam reforming of LPG at 600 °C for 24 hours with a steam to carbon (S/C) molar ratio of 2.0. The main products obtained in the reaction for all the samples were H2 and small amounts of CO and CO2. Only for rhodium containing catalyst the formation of CH4 in very low amounts was observed. The results showed that the catalysts of rhodium and platinum presented high stability against the deposition of carbon for a reforming reaction. However, the nickel and ruthenium catalysts presented large deactivation. The use of the ceria-based support was very important to help to maintain catalytic activity.